Family Support to Improve Maternity Mothers' Success in Early Breastfeeding Initiation - Indrasari, Nelly (Universitas Aisyah Pringsewu, 2023)
Breast milk is the gold standard for baby food; it has been scientifically established to provide benefits that no other food or beverage can match since it includes the most suitable, complete nutrients and constantly adapts to the baby's changing demands. The gold standard for infant nutrition starts with an Early nursing Initiation and continues with six (six) months of exclusive nursing (Munzia, 2013). Only 3.7% of infants in Indonesia are nursed within the first hour of their lives, according to research. There is only one issue with moms not continuing to breastfeed their children until they are six months old: they don't completely understand how to breastfeed well, including procedures and how to obtain breast milk, especially if they also have to work. According to the 2021 Basic Health Research (Riskesdas) findings, the province of Lampung achieves an early breastfeeding initiation rate of 80.4% and an exclusive breastfeeding rate of 73.6% for babies who are 6 months old. Compared to West Tulang Bawang Regency, where the success rate for exclusive breastfeeding was 29.1% rather than the desired 60%, the success rate for early breastfeeding initiation was 1.8% rather than the recommended 39.6%. Early breastfeeding is practiced for all newborns (Riskesdas, 2021).The goal of the study was to ascertain how family support affected the effectiveness of early breastfeeding initiation in 2022 at the PMB Work Area of the West Tulang Bawang Regency Service. In this study, a quasi-experiment with a control group design was used. All women and birth attendants in the West Tulang Bawang District Health Office's service area in 2022 made up the study's population. The 96 birth moms and delivery attendants who worked at the West Tulang Bawang District Health Office in 2022 were the study's sample. Observation, interviews, and documentation studies are used to acquire data. Descriptive and analytical statistics are used to analyse and analyze data.The analysis of the data reveals that respondents who had family assistance were able to initiate early breastfeeding within the first 30 minutes. In contrast, those who had family assistance on average were able to initiate early breastfeeding in the third 30 minutes. According to the statistical test results, p = 0.014, it may be inferred that the effectiveness of early breastfeeding initiation in new moms is significantly influenced by the family's support.Researchers in scientific development may offer the following advice: having a partner present during labor and delivery will have a really exceptional impact, especially on the mother's psychologically. Giving this care will mark the start of a successful nursing relationship, and vice versa. In an effort to increase the coverage of exclusive breast milk and achieve mother and infant health in Tulang Bawang Barat, the results of this research can be continuously improved to provide more pertinent information and learning resources about early breastfeeding initiation. These improvements will also be very helpful for future scientific advancement.